Ecological and biological studies on five-lined skink, Trachylepis (= Mabuya) quinquetaeniata inhabiting two different habitats in Egypt - Kadry, Mohamed A. M.; Mohamed, Hanan R. H.; Hosney, Mohamed (Cellular and Molecular Biology, 2017)
This study was carried out to study the diet type, genetic, morphometric and histological variations between two natural populations of Trachylepis quinquetaeniata inhabiting Abu-Rawash, Embaba, North Giza and Garfas-Senoures, El-Faiyum habitats. In this study, morphometric examination showed that Trachylepis quinquetaeniata is a typically ground-dwelling Skink and seems to be frequently associated with grass and below shrubs. Geographic variation in sexual size dimorphism (SSD) and head size dimorphism (HSD) with greater dimensions in Garfas-Senoures, El-Faiyum compared with Abu-Rawash, Embaba, North Giza might be correlated with spatial food availability and abundance or micro-evolutionary change or phenotypic plasticity. Also, the increase of body size and mass in individuals from Garfas-Senoures, El-Faiyum might be an adaptation to lower ambient temperature and hypoxia. Diet analysis showed that the bulk of gut contents were beetles, plant bugs, hymenopterans and dipterans. The remainder of the plant material was probably ingested secondarily. Moreover, the increase in the activity of Ldh in liver tissues of T. quinquetaeniata inhabiting Abu-Rawash, Embaba, North Giza could be confirmed by the significant increase in the accumulation of the total lipids in liver and muscle tissues than that in the other population. As well as, a marked degeneration, necrosis and desquamation of spermatogoneal cells lining seminiferous tubules in testes of T. quinquetaeniata inhabiting Garfas-Senoures, El-Faiyum than that in the other population inhabiting Abu-Rawash, Embaba, North Giza that could be attributed to the bioaccumulation of soil heavy metals in testes. Higher carbohydrate accumulation in the former lizards’ population was confirmed by the high availability and diversity of diet in El-Faiyum habitat. Thus we concluded that T. quinquetaeniata inhabiting Abu-Rawash, Embaba, North Giza is more active, energetic and adaptable in its habitat than T. quinquetaeniata inhabiting Garfas-Senoures, El-Faiyum.